THE INFLUENCE OF LEADERSHIP STYLE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT ESA SEJAHTERA FOUNDATION - Mulyani Rody Muin; Indra Yonda Syahputra; Sri Wahyuni (UPMI Management, 2022)
This study aims to determine the influence of leadership style and work discipline on employee performance at the ESA Sejahtera Foundation. The population in this study was all permanent employees at the Esa Sejahtera Pekanbaru Foundation, which amounted to 54 people who had the same group level. At the same time, the sample in this study is the total population using a saturated sampling technique (census). The data collection techniques in this study are interviews and questionnaires, with data analysis using descriptive methods and multiple regression. The results of the study show that leadership style and work discipline have a significant effect on employee performance at the ESA Sejahtera Foundation. The contribution of leadership style and work discipline to employee performance was 72.2%, while the remaining 27.8% was determined by other factors not observed in this research model. For this reason, researchers suggest the need for leaders to pay attention to their subordinates, meaning that leaders must be willing to listen and understand what employees want and need. It is necessary always to provide employees with discipline input so that later employees will always come to work on time and not leave the office prematurely. In addition, the company needs to continuously monitor the quality of employee work by requiring each employee to monitor each work in detail and then re-check to prevent errors. JEL Classification: M20, O15, O40